2019
DOI: 10.1039/c9md00148d
|View full text |Cite
|
Sign up to set email alerts
|

Druggability assessment of mammalian Per–Arnt–Sim [PAS] domains using computational approaches

Abstract: Protein dynamics finely tune the “druggability” of mammalian PAS-B domains, as assessed by atomistic molecular dynamics simulations and hotspot mapping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…This short distance reduced the accessible area for both residues from 5 nm 2 to an average 4.2 nm 2 for the replica. A third cysteine C333 is located on the loop 1 region, which should be close to the previously predicted areas to be a druggable binding site [9]. Cypreds were used to evaluate the reactivity and pKa of C300, C316 and C333.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…This short distance reduced the accessible area for both residues from 5 nm 2 to an average 4.2 nm 2 for the replica. A third cysteine C333 is located on the loop 1 region, which should be close to the previously predicted areas to be a druggable binding site [9]. Cypreds were used to evaluate the reactivity and pKa of C300, C316 and C333.…”
Section: Resultsmentioning
confidence: 90%
“…To evaluate the effect of these unstructured terminal segments, we have generated and simulated truncation mutants of human AhR PAS-B domain, where the terminal segments were truncated to various degrees. Atomistic molecular dynamics (MD) simulations showed that the entropic force generated by these unstructured termini segments controls the stability of the entire domain directly, and finely tunes the flexibility of the dimerisation interfaces and the "druggable" sites reported in the previous studies [9]. Subsequently, we extended our AhR PAS-B simulations to other PAS-B domains, to assess whether the observations for AhR might be part of a general trend.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…The interactions between the two PAS A monomers involved two distinctive areas within the A′ α-helices, revealing a strong interaction between Phe115, Leu116, and Ala119 from the A′ α-helix in one monomer with Val124, Phe260, and Ile262 from the β-sheet in the other monomer as shown in Figure 3. The protein structure revealed an undruggable pocket due to hydrophobic residues, and other residues such as Gln112 and Ile262 are essential in the interface for AHR dimerization, either homodimer or heterodimer with ARNT [37,38] Two more additional AhR structures were revealed in 2017 (see Figure 4). The two structures comprise multiple AhR domains and show a clear interaction between AhR and its dimerization partner, ARNT, as well as its interaction with two DNA strands.…”
Section: Ahr Three-dimensional Structuresmentioning
confidence: 99%